Phase-change microcapsule capable of intelligently adjusting temperature and preparation method of fabric of phase-change microcapsule

By forming a temperature-sensitive gel film from N-isopropylacrylamide and acrylic acid copolymer, and combining it with polyether surfactants and organic phase change materials, the problems of slow temperature response, easy coating peeling, and narrow phase change temperature range of smart temperature-regulating fabrics are solved, achieving adaptive temperature regulation and improved durability.

CN121087803APending Publication Date: 2025-12-09LANXI SUBLIMATION TEXTILE

Patent Information

Application Number
CN202511237149.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing intelligent temperature-regulating fabrics suffer from slow temperature response, easy coating peeling, narrow phase change temperature range, and easy leakage of microcapsules, resulting in severe stuffiness in high humidity environments and insufficient durability.

Method used

A temperature-sensitive gel membrane was formed by using N-isopropylacrylamide and acrylic acid copolymer, and polyether surfactants were combined to improve the sensing-response-energy storage performance of microcapsules. A stable microcapsule structure was formed through the synergistic effect of organic phase change materials and fibers.

Benefits of technology

It enables the fabric to adaptively regulate temperature in high humidity environments, reducing stuffiness, improving moisture permeability and durability, and ensuring the continuity and responsiveness of temperature regulation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of textile fabrics, and discloses an intelligent temperature-adjusting phase change microcapsule and a preparation method of a fabric thereof. The phase change microcapsule is prepared from the following components in percentage by mass: 60 to 80 percent of organic phase change material, 6 to 15 percent of N-isopropylacrylamide, 4 to 10 percent of acrylic acid, 1 to 5 percent of polyether surfactant, 2 to 5 percent of urethane acrylate and 2 to 5 percent of initiator. Warp yarn, first weft yarn and second weft yarn containing the microcapsules are woven into the intelligent temperature-adjusting phase-change fiber fabric, the response speed of the phase-change microcapsules is increased through the thermosensitivity of the organic phase-change materials, temperature can be buffered and adjusted in a wide temperature range, the organic phase-change materials cooperate with the temperature-sensitive polymer capsule wall, heat release, warm keeping, ventilation and moisture removal are achieved, and the intelligent temperature-adjusting phase-change fiber fabric is obtained. Inlet of hot air is reduced through heat absorption and cooling, climate and air temperature adjustment is self-adapted, and somatosensory comfort is maintained. In addition, no components irritating to the skin are added in the formula, so that adverse reactions such as sensitization and the like on consumers are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of textile fabric technology, specifically a method for preparing intelligent temperature-regulating phase change microcapsules and their fabrics. Background Technology

[0002] Fabric is the primary material constituting clothing, directly determining its appearance, comfort, and functionality. With technological advancements, people are increasingly emphasizing the functionality of clothing and demanding higher levels of thermal management capabilities. Phase change thermal modulating materials, which can absorb or release heat through phase changes in response to ambient temperature variations, are gradually finding applications in the textile and apparel industry. While years of development have yielded some research results in the development of new phase change thermal modulating materials, existing fabrics still have limitations. For example, their moisture permeability often cannot adaptively adjust to ambient humidity, leading to stuffiness in high-humidity environments. Furthermore, the durability and overall performance of these fabrics need further improvement.

[0003] Existing technologies still have some unresolved problems. For example, patent CN110328938A discloses a smart temperature-regulating viscose fiber fabric. While it uses a coating and microcapsules for synergistic temperature regulation, the coating is prone to peeling off, and the microcapsules are unevenly distributed, resulting in slow temperature response, inconsistent temperature regulation, and a narrow phase change temperature range, making it difficult to meet the needs of different environments. Furthermore, after multiple cycles, the microcapsules are prone to core material leakage, and fatigue cracks easily appear in the capsule walls, leading to functional degradation. This technology has several problems and cannot be widely used.

[0004] In summary, while microcapsule and fiber blending technology is indeed used in the textile fabric industry, it still suffers from problems such as slow temperature response, loose and easily peeling coatings, and a narrow phase change temperature range. Therefore, developing a smart fabric that can simultaneously optimize moisture permeability, temperature control, and structural properties is of great significance. Summary of the Invention

[0005] The purpose of this invention is to provide a smart temperature-regulating phase change microcapsule. This microcapsule not only accelerates the response speed of the phase change microcapsule through the temperature sensitivity of the organic phase change material, thereby reducing the hysteresis of smart temperature regulation in fabrics, but also forms a protective film on the microcapsule surface through an N-isopropylacrylamide and acrylic acid copolymer hydrogel, and adds polyether surfactants to improve the temperature-sensitive gel properties of the microcapsule, thus achieving integrated smart temperature regulation of the microcapsule encompassing "sensing-response-energy storage".

[0006] The objective of this invention is achieved through the following solution: A smart temperature-controlled phase change microcapsule, the composition comprising the following components by mass fraction: 50-90% organic phase change material, 5-20% N-isopropylacrylamide, 3-20% acrylic acid, and 1-10% polyether surfactant.

[0007] Preferably, the composition comprises the following components in the indicated mass fractions: 60-80% organic phase change material, 6-15% N-isopropylacrylamide, 4-10% acrylic acid, 1-5% polyether surfactant, 2-5% polyurethane acrylate, and 2-5% initiator.

[0008] The lower critical solution temperature of the N-isopropylacrylamide (NIPAM)-acrylic acid (AAc) copolymer is 32°C. Its temperature sensitivity stems from the dynamic conformational changes of the molecular chains. At temperatures above 32°C, the hydrophobic isopropyl groups aggregate, and the polymer chains contract to form a dense structure. At temperatures below 32°C, the amide groups of NIPAM bond with water molecules through hydrogen bonds, causing the chain segments to extend and swell. The carboxyl groups (-COOH) of acrylic acid not only form intramolecular hydrogen bonds with the amide groups of NIPAM, enhancing network stability, but also increase the swelling rate through hydrophilicity, enabling the polymer to respond rapidly to changes in ambient temperature.

[0009] NIPAM and AAc polymers synergistically construct a flexible interface layer with polyurethane acrylate (PUA) to form a hydrogel protective film. The urethane bonds (-NH-COO-) in PUA form hydrogen bonds with the hydroxyl / amino groups on the fiber surface. The contact angle between the microcapsules and the fiber reaches 148°, adhering to the fiber without binding to it.

[0010] The carboxyl group (-COOH) of AAc absorbs moisture and ionizes into -COO-. The electrostatic repulsion increases the porosity of the polymer network. The thermosensitive shrinkage of PNIPAM (when the body temperature is >32℃) and the swelling of AAc form a "pump effect", actively expelling sweat and accelerating diffusion.

[0011] Preferably, the organic phase change material is one or both of lauric acid or methyl menthol.

[0012] Lauric acid (melting range 42-44℃) and methyl menthol (melting range 35-37℃) precisely regulate the phase transition temperature to a comfortable range for the human body through a eutectic effect. The long dodecyl chain of lauric acid interacts hydrophobically with the isopropyl group of PNIPAM in the capsule wall through van der Waals forces, enhancing the interfacial binding energy. The methyl ester group (-COOCH3) of methyl menthol forms intermolecular hydrogen bonds with the carboxyl group of AAc, jointly inhibiting phase separation.

[0013] Preferably, the polyether surfactant is a polyoxyethylene-polyoxypropylene-polyoxyethylene (PEO-PPO-PEO) triblock copolymer; the initiator is one or two of ammonium persulfate and azobisisobutyramidine hydrochloride.

[0014] The PPO segments of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer undergo simultaneous dehydration at temperatures above 32°C, synergistically enhancing the hydrophobic effect and accelerating the endothermic response of the phase change material. The PEO end of PEO-PPO-PEO is bonded to the AAc carboxyl group, while the PPO end is anchored to the surface of the hydrophobic polyester fiber. The long-chain polyether segments of PUA interpenetrate with the copolymer network, forming elastic crosslinking points for physical interlocking. The entangled structure of the microcapsule wall encapsulates the fiber, improving the adhesion between the microcapsule and the fabric and reducing microcapsule detachment.

[0015] Sulfate free radicals (SO4) generated by ammonium persulfate - Simultaneously, it initiates the opening of NIPAM and AAc double bonds, resulting in balanced initiation efficiency and uniform copolymer sequence distribution; the decomposition of azobisisobutyramidine hydrochloride generates carbon-centered free radicals, which preferentially attack the carboxyl double bonds of AAc, thereby improving the prepolymerization efficiency.

[0016] This invention also discloses a smart temperature-regulating phase change fiber fabric, in which warp yarns, weft yarn one, and weft yarn two containing the microcapsules are woven into a smart temperature-regulating phase change fiber fabric. This fabric can not only achieve adaptive adjustment in high humidity environments to alleviate stuffiness, but also balance humidity and reduce the stickiness caused by sweat accumulation in traditional fabrics.

[0017] Preferably, the mass ratio of cotton fiber to phase change viscose fiber in the warp yarn is 4:6; the mass ratio of cotton fiber, spandex, and phase change polyester in the first weft yarn is 2:2:6; and the mass ratio of hollow-covered yarn to phase change polyester in the second weft yarn is 3:7.

[0018] Chemical modification of viscose fibers enables them to stably encapsulate phase change materials, preventing microcapsule leakage while maintaining fiber flexibility. Cotton fibers can quickly absorb sweat, reducing stuffiness. Spandex serves as the core yarn, with an outer layer of phase change polyester and cotton blended yarn, protecting the spandex, reducing damage, and extending its service life. The properties of cotton, polyester, and spandex are balanced, and their functions are superimposed after blending. The strength of polyester compensates for the fragility of spandex, the moisture absorption of cotton compensates for the hydrophobicity of polyester, and the elasticity of spandex compensates for the rigidity of cotton and polyester fibers. The lightweight hollow-wrapped yarn reduces the overall weight of the fabric, while the phase change polyester provides high strength and abrasion resistance, compensating for the low strength of hollow fibers.

[0019] Preferably, the empty-wrapped yarn is an empty-wrapped elastic integral yarn composed of PTT100D / 72F semi-dull polyester and 70D spandex yarn, and the phase change polyester is a phase change polyester composed of DTY100D / 72F semi-dull polyester and 70D spandex.

[0020] 70D is a medium-fine denier yarn, which is lightweight, soft, and more resistant to friction. The hollow structure of the hollow-wrapped elastic integrated yarn can provide static insulation, compensating for the insufficient temperature regulation of phase change materials in static environments. The PTT molecular chain has a helical structure, naturally possessing elasticity similar to spandex. This works synergistically with the elasticity of the hollow-wrapped yarn to reduce the amount of spandex used. The 100D fiber density provides sufficient fiber volume to ensure that the phase change microcapsule content meets the standards. The high F number makes the fiber softer and the fabric has good drape. The semi-dull treatment can reduce the fiber reflectivity, making it suitable for everyday clothing.

[0021] A method for preparing the above-mentioned intelligent temperature-regulating phase change fiber fabric includes the following steps: S1, After stirring and melting the organic phase change material, nano-SiO2 is added to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved, an initiator is added and the temperature is lowered, then polyether surfactant and polyurethane acrylate are added, and the pH is adjusted to obtain a composite capsule wall solution. S3, the oil phase solution is dropped into the composite capsule wall solution, solidified, centrifuged, washed and dried to obtain modified phase change microcapsules; S4. Microcapsules are mixed with viscose fibers and then blended with cotton fibers to obtain warp yarn; microcapsules are mixed with polyester and then blended with cotton fibers, and then coated with spandex to obtain weft yarn one; microcapsules are mixed with polyester and then twisted with empty wrapped yarn to obtain weft yarn two, and the fabric is woven to obtain phase change fiber fabric.

[0022] Preferably, the specific conditions in step S2 are as follows: N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the temperature-sensitive copolymer prepolymer is prepolymerized at 70-80°C for 30-40 minutes; after cooling to 40-50°C, polyether surfactants and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution.

[0023] Ammonium persulfate has a conversion rate of >95% at 70-80℃, ensuring continuous free radical generation. At this temperature, the copolymer chains are in a contracted state, avoiding premature swelling that could lead to an excessively wide molecular weight distribution. The reaction time is controlled within 40 minutes to avoid excessive crosslinking that could lead to gelation, which would be detrimental to the subsequent addition of polyethers and polyurethanes. Adding polyether surfactants at 40-50℃ facilitates the penetration and anchoring of PP segments. The -COOH of AAc forms a dynamic hydrogen bond network with the PEO segments of polyether, improving solution homogeneity. At 40-50℃, the acrylate double bonds of PUA can still participate in the residual free radical reaction, but excessive crosslinking caused by high temperatures (>60℃) should be avoided.

[0024] Preferably, the specific conditions in step S3 are as follows: the oil phase solution is slowly dripped into the composite capsule wall solution, and after reacting at 60-70°C for 4-6 hours under a nitrogen atmosphere, it is solidified to form a core-shell structured microcapsule suspension; the suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0025] A temperature of 60-70℃ ensures that the microcapsules are in a liquid state, which facilitates uniform encapsulation by the wall material; at the same time, it promotes the condensation reaction of the wall material, forming a dense cross-linked network, generating a complete core-shell structure, and increasing the loading capacity of the phase change microcapsules.

[0026] The beneficial effects of this invention are as follows: This product uses N-isopropylacrylamide and acrylic acid copolymers to prepare microcapsule walls, which are then infused with organic phase change materials. These materials are then blended with textile fibers to create a smart temperature-regulating fabric. The organic phase change microcapsules can buffer and regulate temperature over a wide temperature range, working synergistically with the temperature-sensitive polymer capsule walls to release heat for warmth, breathability, and moisture wicking, while absorbing heat for cooling and reducing the entry of hot air. This adaptive temperature regulation maintains a comfortable user experience. Furthermore, this formula contains no skin-irritating ingredients and does not cause allergic reactions or other adverse reactions in consumers. Detailed Implementation

[0027] Example 1: This embodiment provides a smart temperature-controlled phase change microcapsule, specifically comprising the following components by mass fraction: 65% organic phase change material, 8% N-isopropylacrylamide, 6% acrylic acid, 4% polyether surfactant, 4% polyurethane acrylate, and 3% initiator.

[0028] The organic phase change material is 30% lauric acid and 35% methyl menthol; the polyether activator is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; and the initiator is 2% ammonium persulfate and 1% azobisisobutyramidine hydrochloride.

[0029] This embodiment also provides a method for preparing intelligent temperature-controlled phase change microcapsules, specifically including the following steps: S1, after the organic phase change material is stirred and melted at 60-70℃, nano-SiO2 is added and stirred to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the reaction is carried out at 70-80℃ for 30-40 minutes to produce a temperature-sensitive copolymer prepolymer solution; after cooling to 40-50℃, polyether surfactants and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution. S3. The oil phase solution is slowly dripped into the composite capsule wall solution. Under a nitrogen atmosphere, the reaction is carried out at 60-70℃ for 4-6 hours and then solidified to form a core-shell structured microcapsule suspension. The suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0030] Example 2: This embodiment provides a smart temperature-controlled phase change microcapsule, specifically comprising the following components by mass fraction: 65% organic phase change material, 8% N-isopropylacrylamide, 6% acrylic acid, 4% polyether surfactant, 4% polyurethane acrylate, and 3% initiator.

[0031] The organic phase change material is 25% lauric acid and 40% methyl menthol; the polyether activator is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; and the initiator is 2% ammonium persulfate and 1% azobisisobutyramidine hydrochloride.

[0032] This embodiment also provides a method for preparing intelligent temperature-controlled phase change microcapsules, specifically including the following steps: S1, after the organic phase change material is stirred and melted at 60-70℃, nano-SiO2 is added and stirred to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the reaction is carried out at 70-80℃ for 30-40 minutes to produce a temperature-sensitive copolymer prepolymer solution; after cooling to 40-50℃, polyether surfactants and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution. S3. The oil phase solution is slowly dripped into the composite capsule wall solution. Under a nitrogen atmosphere, the reaction is carried out at 60-70℃ for 4-6 hours and then solidified to form a core-shell structured microcapsule suspension. The suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0033] Example 3: This embodiment provides a smart temperature-controlled phase change microcapsule, specifically comprising the following components by mass fraction: 65% organic phase change material, 8% N-isopropylacrylamide, 6% acrylic acid, 4% polyether surfactant, 4% polyurethane acrylate, and 3% initiator.

[0034] The organic phase change material is 35% lauric acid and 30% methyl menthol; the polyether activator is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; and the initiator is 2% ammonium persulfate and 1% azobisisobutyramidine hydrochloride.

[0035] This embodiment also provides a method for preparing intelligent temperature-controlled phase change microcapsules, specifically including the following steps: S1, after the organic phase change material is stirred and melted at 60-70℃, nano-SiO2 is added and stirred to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the reaction is carried out at 70-80℃ for 30-40 minutes to produce a temperature-sensitive copolymer prepolymer solution; after cooling to 40-50℃, polyether surfactants and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution. S3. The oil phase solution is slowly dripped into the composite capsule wall solution. Under a nitrogen atmosphere, the reaction is carried out at 60-70℃ for 4-6 hours and then solidified to form a core-shell structured microcapsule suspension. The suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0036] Comparative Example 1: This comparative example provides a smart temperature-controlled phase change microcapsule, specifically comprising the following components by mass fraction: 65% organic phase change material, 8% N-isopropylacrylamide, 6% acrylic acid, 4% polyether surfactant, 4% polyurethane acrylate, and 3% initiator.

[0037] The organic phase change material is 30% paraffin and 35% fatty acid ester; the polyether activator is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; and the initiator is 2% ammonium persulfate and 1% azobisisobutyramidine hydrochloride.

[0038] This embodiment also provides a method for preparing intelligent temperature-controlled phase change microcapsules, specifically including the following steps: S1, after the organic phase change material is stirred and melted at 60-70℃, nano-SiO2 is added and stirred to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the reaction is carried out at 70-80℃ for 30-40 minutes to produce a temperature-sensitive copolymer prepolymer solution; after cooling to 40-50℃, polyether surfactants and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution. S3. The oil phase solution is slowly dripped into the composite capsule wall solution. Under a nitrogen atmosphere, the reaction is carried out at 60-70℃ for 4-6 hours and then solidified to form a core-shell structured microcapsule suspension. The suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0039] The difference between this comparative example and Example 1 is that the organic phase change material in this comparative example is replaced with paraffin and fatty acid ester.

[0040] Comparative Example 2: This comparative example provides a smart temperature-controlled phase change microcapsule, specifically comprising the following components by mass fraction: 65% organic phase change material, 8% N-isopropylacrylamide, 6% acrylic acid, 4% silane coupling agent, 4% polyurethane acrylate, and 3% initiator.

[0041] The organic phase change material is 30% lauric acid and 35% methyl menthol; the silane coupling agent is 2% aminosilane and 2% epoxysilane; the initiator is 2% ammonium persulfate and 1% azobisisobutyramidine hydrochloride.

[0042] This embodiment also provides a method for preparing intelligent temperature-controlled phase change microcapsules, specifically including the following steps: S1, after the organic phase change material is stirred and melted at 60-70℃, nano-SiO2 is added and stirred to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved in a certain proportion, an initiator is added, and the reaction is carried out at 70-80℃ for 30-40 minutes to produce a temperature-sensitive copolymer prepolymer solution. After cooling to 40-50℃, a hydrolyzed silane coupling agent solution and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution; S3. The oil phase solution is slowly dripped into the composite capsule wall solution. Under a nitrogen atmosphere, the reaction is carried out at 60-70℃ for 4-6 hours and then solidified to form a core-shell structured microcapsule suspension. The suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0043] The difference between this comparative example and Example 1 is that the polyether surfactant is replaced with a silane coupling agent in this comparative example.

[0044] Comparative Example 3: This comparative example provides a smart temperature-controlled phase change microcapsule, specifically comprising the following components by mass fraction: 65% organic phase change material, 8% N-isopropylacrylamide, 6% acrylic acid, 4% polyether surfactant, 4% polydimethylsiloxane, and 3% initiator.

[0045] The organic phase change material is 30% lauric acid and 35% methyl menthol; the polyether activator is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; and the initiator is 2% ammonium persulfate and 1% azobisisobutyramidine hydrochloride.

[0046] This embodiment also provides a method for preparing intelligent temperature-controlled phase change microcapsules, specifically including the following steps: S1, after the organic phase change material is stirred and melted at 60-70℃, nano-SiO2 is added and stirred to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the temperature-sensitive copolymer prepolymer is prepolymerized at 70-80℃ for 30-40 minutes; after cooling to 40-50℃, polyether surfactant and polydimethylsiloxane are added, and the pH is adjusted to neutral to obtain the composite capsule wall solution. S3. The oil phase solution is slowly dripped into the composite capsule wall solution. Under a nitrogen atmosphere, the reaction is carried out at 60-70℃ for 4-6 hours and then solidified to form a core-shell structured microcapsule suspension. The suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

[0047] The difference between this comparative example and Example 1 is that polyurethane acrylate is replaced with polydimethylsiloxane in this comparative example.

[0048] Experimental Example 1: This experimental example is the performance test of phase change microcapsules of Examples 1-3 and Comparative Examples 1-3. The results are shown in Table 1.

[0049] The following tests are performance tests of phase change microcapsules in Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3. The specific steps include: uniformly dispersing phase change microcapsules in silicone oil, and taking pure silicone oil (without microcapsules) as a control group for baseline correction.

[0050] DSC test: The temperature is increased from 10℃ to 50℃ at a rate of 5℃ / min, and the peak temperature and start / end temperature of the endothermic peak are recorded. The temperature is then slowly decreased from 50℃ to 10℃, and the peak temperature and start / end temperature of the exothermic peak are recorded.

[0051] Constant temperature environment test: The initial temperature of the microcapsule sample was set to 25℃ and placed in a constant temperature environment of 32℃. The temperature and time changes were recorded until the microcapsule temperature reached equilibrium. The temperature difference ΔT1 was calculated as 32℃ - the lowest temperature of the sample. After the microcapsule sample was preheated to 32℃, it was transferred to 22℃. The temperature and time changes were recorded until the microcapsule temperature reached equilibrium. The temperature difference ΔT2 was calculated as the highest temperature of the sample - 22℃.

[0052] Table 1: Performance Testing of Phase Change Microcapsules Example Maximum heat absorption temperature difference (°C) Maximum heat release temperature difference (°C) Heat absorption temperature difference at 32℃ (°C) Heat release temperature difference at 22℃ (°C) Example 1 8.1 7.9 6.8 6.9 Example 2 7.7 7.8 6.7 6.6 Example 3 7.8 7.9 6.8 6.7 Comparative Example 1 7.4 7.2 6.2 6.0 Comparative Example 2 7.2 7.0 6.3 6.0 Comparative Example 3 7.5 7.1 6.1 6.2

[0053] Under all test conditions, in the maximum endothermic temperature difference test, Example 1 achieved a significant temperature difference of 8.1°C. This value is not only significantly higher than all comparative examples (the highest value in Comparative Examples 1-3 is 7.5°C), but also superior to Examples 2 (7.7°C) and 3 (7.8°C) in the same group. This indicates that the phase change material formulation used in Example 1 has a stronger heat absorption capacity in high-temperature environments and can more effectively reduce body surface temperature. In the maximum exothermic temperature difference test, Example 1 improved by nearly 10% compared to the highest value of the comparative examples (7.2°C), demonstrating its equally significant ability to release stored heat in low-temperature environments.

[0054] In specific temperature tests that more closely resemble actual wearing environments, Example 1 achieved a heat absorption temperature difference of 6.8°C at 32°C and a heat release temperature difference of 6.9°C at 22°C, both of which are the highest values ​​among all samples. Of particular note is that in the 22°C test, Example 1's heat release temperature difference was 15% higher than the worst-performing Comparative Example 2 (6.0°C), indicating a more sensitive dynamic temperature control response and optimal temperature regulation effect. This difference translates to longer-lasting warmth and a more comfortable user experience in practical applications.

[0055] From the perspective of material formulation, although the proportions of organic phase change materials (lauric acid and methyl menthol) were slightly adjusted in Examples 2 and 3, the test results showed that these adjustments had a relatively limited impact on the overall performance. The temperature difference between the three examples remained within 0.3℃, indicating that there is an optimal range for the ratio of lauric acid to methyl menthol. The formulation in Example 1 represents the optimal balance point within this range, enabling it to maintain its leading position in all tests.

[0056] In summary, the reason why Example 1 was able to exhibit the best temperature regulation effect may be that: (1) the selection and ratio of 30% lauric acid and 35% methyl menthol achieved the optimal synergistic effect; (2) the phase change material ratio had better dispersion and stability in the fabric; and (3) the phase change temperature range after being mixed in the correct ratio was more in line with the human body's comfortable temperature range.

[0057] Comparative Example 1, where the organic phase change material was replaced with paraffin and fatty acid esters, showed the lowest temperature difference in the test. Lauric acid and methyl menthol exhibit a low eutectic effect; when mixed, they can form a eutectic system, lowering the phase change temperature and widening the temperature control range. Lauric acid provides the energy storage basis, while methyl menthol enhances low-temperature responsiveness. In contrast, paraffin and fatty acid esters, as common phase change materials, exhibit different characteristics. Paraffin has low thermal conductivity and high crystallinity, while fatty acid esters are prone to migration, disrupting the integrity of microcapsules and resulting in low phase change efficiency. Consequently, the temperature difference is significantly lower than that of the lauric acid and methyl menthol composite.

[0058] In Comparative Example 2, replacing polyether surfactants with silane coupling agents resulted in a decrease in temperature difference. The triblock structure of PEO-PPO-PEO exhibited alternating hydrophilic and hydrophobic properties, with PPO (hydrophobic segments) binding to the microcapsule core and PEO (hydrophilic segments) extending outward to form a stable core-shell structure. This structure effectively encapsulates the microcapsules and prevents aggregation. In contrast, silane coupling agents, through their silanol groups (Si-OH), bind to the substrate, improving interfacial adhesion but exhibiting poor dispersibility and failing to form micellar structures. This leads to uneven microcapsule size and hindered heat transfer. Continuous polyether segments, on the other hand, construct a heat conduction path that runs through the microcapsules, promoting rapid heat transfer to the microcapsule core and shortening the response time.

[0059] In Comparative Example 3, replacing polyurethane acrylate with polydimethylsiloxane resulted in a decrease in performance. Polyurethane acrylate forms a flexible cross-linked network that can withstand more than 500 bending cycles, preventing microcapsule rupture. The acrylate groups form chemical bonds with the surface of the microcapsules. Polydimethylsiloxane has poor compatibility with microcapsules, increasing interfacial thermal resistance. Furthermore, the excessive hydrophobicity of polydimethylsiloxane can lead to leakage of phase change microcapsules.

[0060] In summary, phase change microcapsules prepared using formulations containing organic phase change materials (lauric acid and methyl menthol), N-isopropylacrylamide, acrylic acid, polyether surfactants (polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer), polyurethane acrylates, and initiators (ammonium persulfate and azobisisobutyramidine hydrochloride) exhibit superior performance.

[0061] Experimental Example 2: This experimental example is a performance test of the phase change fiber fabric prepared by phase change microcapsules in Examples 1-3. The results are shown in Table 2.

[0062] The following fabric testing experiments were conducted on phase change fiber fabrics prepared from phase change microcapsules in Examples 1, 2, and 3. The specific steps included: mixing microcapsules with viscose fibers, then blending cotton fibers and phase change viscose fibers at a mass ratio of 4:6 to obtain warp yarns; mixing microcapsules with polyester, then blending with cotton fibers, then covering with spandex, and blending cotton fibers, spandex, and phase change polyester at a mass ratio of 2:2:6 to obtain weft yarn one; mixing microcapsules with polyester, then twisting empty-covered yarn and phase change polyester at a mass ratio of 3:7 to obtain weft yarn two, and then weaving the fabric using a double structure weaving process to obtain the phase change fiber fabric.

[0063] Fabric thermal insulation rate test: Place the fabric to be tested in a constant temperature and humidity environment for 24 hours to equilibrate. Cut three 20cm×20cm samples respectively. Set the hot plate temperature to 35℃. Place a pure cotton standard reference fabric and expose the hot plate. Record the heat flow Q0 after stabilization. Cover the hot plate with the fabric to be tested and wait for the heat flow to stabilize. Record Q1. Repeat the test 3 times and take the average value. Calculate the thermal insulation rate = (1-Q1 / Q0)×100%.

[0064] Water vapor transmission rate test: Place the fabric to be tested in a constant temperature and humidity environment for 24 hours to equilibrate. Cut three 20cm×20cm samples and fix them in the middle of the test chamber. Control the temperature on one side at 32℃ and the temperature on the other side at 22℃. Start the infrared sensor to monitor the water vapor transmission rate in real time. Repeat the test 3 times and take the average value.

[0065] Temperature response speed test: The fabric to be tested was placed in a constant temperature and humidity environment for 24 hours to equilibrate. Three 20cm×20cm samples were cut out respectively. The fabric was flat and covered with the hot plate. The hot plate was quickly switched to the target temperature of 32℃ and 22℃. The infrared thermal imager and embedded sensor were started simultaneously and Δt was recorded.

[0066] Table 2: Performance Testing of Phase Change Fiber Fabrics Example Thermal insulation rate (%) Water vapor transmission (g / m 2 ·24h) Temperature response speed (s) Example 1 76 3650 106 Example 2 73 3580 100 Example 3 74 3590 110

[0067] Example 1 demonstrates the highest heat retention rate. 30% lauric acid forms a stable crystalline thermally conductive framework, providing sufficient phase change enthalpy, while 35% methyl menthol optimizes the distribution of amorphous regions, preventing excessive crystallization from clogging fiber gaps. It also exhibits optimal air permeability, with moderate 35% methyl menthol reducing intermolecular forces, facilitating water vapor diffusion. Simultaneously, the PEO-PPO-PEO triblock copolymer regulates the hydrophilic-hydrophobic balance, forming a continuous porous structure. Furthermore, it provides balanced response speeds, with the low viscosity of methyl menthol promoting liquid heat transfer, and the lauric acid crystalline network maintaining structural stability. The optimal ratio of 30% lauric acid to 35% methyl menthol ensures a continuous heat conduction path while preventing excessive crystal growth that could decrease air permeability.

[0068] Example 2 showed the fastest response speed. 40% methyl menthol reduced the viscosity of the system, forming a more continuous liquid heat transfer channel. Insufficient 25% lauric acid resulted in an incomplete crystalline network, and excessive methyl menthol accelerated liquid heat transfer due to its low viscosity. The plasticizing effect weakened the intermolecular forces, leading to a decrease in heat retention. Excessive methyl menthol caused excessive softening of the amorphous region, resulting in the collapse of some micropores and slightly lower air permeability.

[0069] Example 3 has a moderate heat retention rate. 35% lauric acid increases crystallinity, but excessive crystallization leads to increased grain boundary thermal resistance. The air permeability is moderate. Due to the increased crystal domain of lauric acid, the channels of amorphous regions are compressed. However, since 30% of methyl menthol is retained, the pores are not completely blocked, so it is better than Example 2. The response speed is the slowest. High crystallinity delays phase transformation kinetics, resulting in a decrease in dynamic response capability.

Claims

1. A smart temperature-regulating phase change microcapsule, characterized in that, The microcapsules comprise the following components by mass fraction: 50-90% organic phase change material, 5-20% N-isopropylacrylamide, 3-20% acrylic acid, and 1-10% polyether surfactant.

2. The intelligent temperature-regulating phase change microcapsule according to claim 1, characterized in that, The microcapsules comprise the following components by mass fraction: 60-80% organic phase change material, 6-15% N-isopropylacrylamide, 4-10% acrylic acid, 1-5% polyether surfactant, 2-5% polyurethane acrylate, and 2-5% initiator.

3. The intelligent temperature-regulating phase change microcapsule according to claim 1 or 2, characterized in that, The organic phase change material is one or both of lauric acid or methyl menthol.

4. The intelligent temperature-regulating phase change microcapsule according to claim 2, characterized in that, The polyether surfactant is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; the initiator is one or two of ammonium persulfate and azobisisobutyramidine hydrochloride.

5. A smart temperature-regulating phase change fiber fabric, characterized in that, Based on the intelligent temperature-regulating phase change microcapsules according to any one of claims 1-4, the warp yarns, weft yarn one, and weft yarn two containing the microcapsules are woven into an intelligent temperature-regulating phase change fiber fabric.

6. The intelligent temperature-regulating phase change fiber fabric according to claim 5, characterized in that, The mass ratio of cotton fiber to phase change viscose fiber in the warp yarn is 4:6; the mass ratio of cotton fiber, spandex, and phase change polyester in the first weft yarn is 2:2:6; and the mass ratio of hollow-covered yarn to phase change polyester in the second weft yarn is 3:

7.

7. The intelligent temperature-regulating phase change fiber fabric according to claim 6, characterized in that, The empty-wrapped yarn is an empty-wrapped elastic integral yarn composed of PTT100D / 72F semi-dull polyester and 70D spandex yarn, and the phase change polyester is a phase change polyester composed of DTY100D / 72F semi-dull polyester and 70D spandex.

8. A method for preparing the intelligent temperature-regulating phase change fiber fabric according to any one of claims 5-7, characterized in that, Includes the following steps: S1, After stirring and melting the organic phase change material, nano-SiO2 is added to form a stable oil phase; S2, N-isopropylacrylamide and acrylic acid are mixed and dissolved, an initiator is added and the temperature is lowered, then polyether surfactant and polyurethane acrylate are added, and the pH is adjusted to obtain a composite capsule wall solution. S3, the oil phase solution is dropped into the composite capsule wall solution, solidified, centrifuged, washed and dried to obtain modified phase change microcapsules; S4. Microcapsules are mixed with viscose fibers and then blended with cotton fibers to obtain warp yarn; microcapsules are mixed with polyester and then blended with cotton fibers, and then coated with spandex to obtain weft yarn one; microcapsules are mixed with polyester and then twisted with empty wrapped yarn to obtain weft yarn two, and the fabric is woven to obtain phase change fiber fabric.

9. The method for preparing the intelligent temperature-regulating phase change fiber fabric according to claim 8, characterized in that, The specific conditions in step S2 are as follows: N-isopropylacrylamide and acrylic acid are mixed and dissolved in proportion, an initiator is added, and the temperature-sensitive copolymer prepolymer is prepolymerized at 70-80℃ for 30-40 minutes; after cooling to 40-50℃, polyether surfactants and polyurethane acrylate are added, and the pH is adjusted to neutral to obtain a composite capsule wall solution.

10. The method for preparing the intelligent temperature-regulating phase change fiber fabric according to claim 8, characterized in that, The specific conditions in step S3 are as follows: the oil phase solution is slowly dripped into the composite capsule wall solution, and after reacting at 60-70℃ for 4-6 hours under a nitrogen atmosphere, it is solidified to form a core-shell structured microcapsule suspension; the suspension is centrifuged, washed, and vacuum dried to obtain modified phase change microcapsules.

Citation Information

Patent Citations

  • Intelligent temperature regulation viscose fiber fabric

    CN110328938A

Cited By

  • Antibacterial composite material with self-refreshing function and preparation method thereof

    CN121675235A